"This is an American Newspaper": Editorial Opinions and the German Immigrant Press in 1917. Issue 2 (3rd April 2021) - Fondren, Elisabeth
Abstract : In 1917, after the United States joined the war in Europe and was no longer politically neutral, on the American front, the German ethnic press became a target for censors and critics. The general assumption was that German language papers bred disloyalty among German immigrant communities and posed a threat to the United States' war efforts. This study explores the editorial and political views of the German-language press during the summer of 1917 by assessing the tone of a sample of German language mainstream newspapers during July 1, 1917 through September 30, 1917. The findings show that the overall coverage was less loyal to Imperial Germany than had been argued by U.S. officials and censors. In an effort to assimilate, German immigrant newspapers widely published the U.S. government's official position, showed support for the American war effort, and focused on cultural affairs of the immigrant community.